Modern sculpture and the question of status - Irene Gras Valero (Col·lecció Singularitats, 2018)
One of the most fascinating yet least explored questions in art history is that of status in art. The analysis of how artists and artworks achieve recognition or not, both during their lifetimes and beyond, leads us into sociology of art, a field that, regarding modern sculpture, has received little attention internationally, and is largely untouched in terms of the Catalan and Spanish contexts. This objective of this volume is to contribute to our understanding of the mechanisms of status and success in nineteenth- and twentieth-century sculpture, especially in Spain and Catalonia. The authors, experts from Europe and America, address the topic both from theoretical viewpoints, and considering the impact on the construction of artists' careers. They also explore the possibilities of sculpture as an object on the path to artistic recognition, and the particularities of status in specific historical circumstances, such as under Franco's dictatorship, in which art is not always put at the service of an ideology.